Budidaya Lebah Madu Trigona pada KTH “Maju Berkah” Dusun Apit Aiq Batulayar - Lombok Barat - Dewi Rispawati; Mey Susanti AS; Siti Yulianah M. Yusuf; Vidya Yanti Utami; Basuki Srihermanto (UNIVERSITAS MUHAMMADIYAH MATARAM, 2021)
This Community Service is entitled